RWA algorithm based on cost of photoelectric conversion device - Daoyun HU; Zhentai YANG; Qianchun LU; Jin QI (Dianxin kexue)
Over the past decade,carrier operator implement fine-grained traffic scheduling in optical transport network(OTN) by deploying optical-electric conversion(OEO) devices on ROADM,which can improve the spectrum utilization.However,OEO device is very expensive,which will increase the CAPEX and OPEX of carrier operator.A problem about traffic scheduling and the deployment of OEO devices in OTN was proposed.Then,the ILP model of this problem was built and it was proved NP-hard.Additionally,two novel algorithms named OEO-RWA and SA-RWA were proposed.At last,these algorithms were demonstrated can not only ensure flexibility of traffic scheduling,but also can reduce the number of OEO device through simulation.